Validation of Suitable Reference Genes for RT-qPCR Data in Achyranthes bidentata Blume under Different Experimental Conditions - Li, Jinting; Han, Xueping; Wang, Can; Qi, Wanzhen; Zhang, Weiyu; Tang, Li; Zhao, Xiting (Frontiers in Plant Science, 2017)
Real-time quantitative polymerase chain reaction (RT-qPCR) is a sensitive technique for gene expression studies. However, choosing the appropriate reference gene is essential to obtain reliable results for RT-qPCR assays. In the present work, the expression of 8 candidate reference genes, EF1-α (Elongation factor 1-α), GAPDH (glyceraldehyde 3-phosphate dehydrogenase), UBC (Ubiquitin-conjugating enzyme), UBQ (Polyubiquitin), ACT (Actin), β-TUB (β-tubulin), APT1 (Adenine phosphoribosyltransferase 1), and 18S rRNA (18S ribosomal RNA), was evaluated in Achyranthes bidentata samples using two algorithms, geNorm and NormFinder. The samples were classified into groups according to developmental stages, various tissues, stresses (cold, heat, drought, NaCl), and hormone treatments (MeJA, IBA, SA). Suitable combination of reference genes for RT-qPCR normalization should be applied according to different experimental conditions. In this study, EF1-α, UBC and ACT genes were verified as the suitable reference genes across all tested samples. To validate the suitability of the reference genes, we evaluated the relative expression of CAS, which is a gene that may be involved in phytosterol synthesis. Our results provide the foundation for gene expression analysis in A. bidentata and other species of Amaranthaceae.